Athletic performance and weight changes during the "Marathon of sands" in athletes well-trained in endurance - Zouhal, H.; Grussard, C.; Vincent, S.; Jacob, C.; Abderrahman, A. B.; Delamarche, P.; Gratas-Delamarche, A. (International Journal of Sports Medicine, 2009)
The purpose of this study is to examine the effects of the "Marathon of Sands" (MS), a 7-day, self-sufficient-diet, multi-stage running race across a section of the Moroccan desert, on body weight and plasma volume variation (PVV) and the relationship of these factors to performance in athletes who are well-trained in endurance. Sixteen MS runners agreed to participate in this study. Weight and body composition were measured and venous blood samples were taken before the first stage (D0), after the third stage (D3) and at the end of the MS (after the sixth stage: D6). Haematocrit and haemoglobin were used to calculate PVV at (D0, D3, and D6). No significant plasma volume decrease was observed throughout the race. Significant decreases in total body weight (BW), fat-free mass (FFM) and fat mass (FM) were observed in D3 and D6 (-4.3%, -3.5%, -0.8%; and -6.1%, -5%, -1.1%, respectively, for BW, FFM and FM at D3 and D6). This study clearly shows that, despite extreme conditions, the MS did not lead to a significant PV decrease in athletes well-trained in endurance. This study also supports the hypothesis that significant body weight loss may not systematically affect performances during long duration multiple-stage races.